Pembuatan Alat Tes Usap Untuk Penentuan Faktor Pindah Pada Pemantauan Kontaminasi Radioaktif Permukaan - Perpustakaan UGM, i-lib ([Yogyakarta] : Kantor Wakil Rektor Bidang Kemahasiswaan dan Alumni UGM, 2003)
The making of smear test devices has been done to decrease uncertainty in the fraction of removed surface contaminant because of personal variations in the sampling technique and the pressure manually applied to the smeared area. In this research, a smear test device was made by using components which are easily available in the market and relatively cheap. The device was tested for the performance and stability by methods of pressure variations and activity contaminant variations at the same pressure. The relationship among these parameters was searched. The performance of this device is between the pressure area of 1.0334 g/cm2 to 20.6688 g/cm2. The relationship between variations of the pressure (x) and Removal Factor (y) is y =0.4997x+2.209 with R2 = 0.9865 and the mean of relative error = 6.0125 % in pressure range of 1.0334 to 20.6688 g/cm2. The relationshy, between variation contaminant activity (x) in the same pressure and Removal Factor (y) is y = 4.10-5 x + 5.9541 with R = 0.0712 and the mean of relative error = 1.9783 % in activity range of 45.6874 to 3210.1238 Bq. The value of mean relative error is small, indicating the stability of device and its feasibility for use.